Global illumination for static and dynamic objects using light probes - Bowald, Johan (My University, 2016)
Today, real-time 3D applications commonly use two separate techniques for global illumination of static and dynamic objects. Using two different systems such as lightmaps and point clouds (probe-based solutions) can lead to different appearances depending on the type of object. The purpose of this thesis project has been to research and develop a data structure used to sample indirect light for both static and dynamic objects. Integrating the indirect light data for static objects in a probebased solution has additional advantages over lightmaps. For example, an artist will be able to apply small changes to a level and instantly have an adequate perception of the global illumination. A data structure has been implemented in Autodesk’s game engine, Stingray, and tested on three different scenes. The data structure uses symterical probe placement, a method to filter out occluded probes, and 3rd order spherical harmonics as transfer basis. The data structure can be run in real time while being memory efficient. However, visual artifacts arise for complex geometry, such as spheres. Even if this project did not achieve the visual quality strived for, its findings can be used when developing a better solution.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science